Developing a transition workshop for adolescents with sickle cell disease - James Bradley; Zelyn Lee; Melina Cheong (Health Care Transitions)
Background: The transfer from paediatric to adult care presents a significant challenge for adolescents and young adults (AYA) with sickle cell disease (SCD). Disease self-management skills have been recognized as important mediators of poor health outcomes, but transition-related skills such as scheduling appointments and understanding the shift in health care responsibilities remain under taught in the healthcare system. The purpose of this quality improvement (QI) study was to (1) understand the areas of disease self-management that AYA patients felt underprepared for, and (2) design and evaluate an educational program addressing the top unmet skills. Methods: The Plan-Do-Study-Act (PDSA) model was implemented in a tertiary outpatient clinic between September 2020 and July 2021. Patients were surveyed during regular clinic visits to identify their priorities on disease self-management skills. Based on the results, a virtual workshop was created and administered three separate times. Feedback was collected using an electronic survey. Results: ‘Navigating the adult health care system’ was the top self-management skill that AYA patients (n = 39) identified needing more support with. The majority of participants (79%, n = 14) reported that the virtual workshop was excellent, with ‘appointment management’ being the most useful topic discussed. Participants also reported feeling more confident (71%) and aware (86%) of how to navigate adult care. Conclusion: This QI study showed that delivering a virtual workshop on transition skills was well received by AYA participants with SCD. The PDSA framework was useful for identifying specific knowledge gaps in transition aged AYA to help improve patient education in a well-established transition program.